1995
DOI: 10.1007/bf00027062
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate tolerance in maize (Zea mays L.). 1. Differential response among inbred lines

Abstract: Variation in susceptibility to the safe broad-spectrum herbicide glyphosate was investigated in maize . Eleven inbred lines, grown in a growth chamber, were evaluated for their tolerance to the herbicide at 2 .4 mM (0 .2 kg a .i . in 400 1 ha ' of water) . Following treatment with glyphosate at the three-leaf stage, significant variation in damage, expressed as visual injury ratings scored 7, 14 and 21 days after the application of the herbicide, was found . Effects on dry weight and shoot height were consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Families displayed a continuum of responses to glyphosate, ranging from susceptible to tolerant, thus suggesting a complex genetic control of the trait . Moreover, contrary to the results obtained as to the natural variability of maize inbreds for the sensitivity to glyphosate (Forlani & Racchi, 1995), the percent reduction in dry weight was poorly correlated with the relative tolerance assessed as visual rating (r = 0 .196 NS , n= 11) .…”
Section: Screening Of Somaclones For Glyphosate Tolerancecontrasting
confidence: 47%
See 3 more Smart Citations
“…Families displayed a continuum of responses to glyphosate, ranging from susceptible to tolerant, thus suggesting a complex genetic control of the trait . Moreover, contrary to the results obtained as to the natural variability of maize inbreds for the sensitivity to glyphosate (Forlani & Racchi, 1995), the percent reduction in dry weight was poorly correlated with the relative tolerance assessed as visual rating (r = 0 .196 NS , n= 11) .…”
Section: Screening Of Somaclones For Glyphosate Tolerancecontrasting
confidence: 47%
“…Though so far a direct action of glyphosate on photosynthesis has not been demonstrated (Cole, 1985), data obtained on maize inbreds clearly showed the carbon-exchange rate as an early and sensitive index of glyphosate injury, and indicated that differences in response for CER fit the differences in the overall sensitivity to the herbicide (Forlani & Racchi, 1995) . Also in this case the most tolerant family exhibits a capacity to maintain a high level of CER, contrary to what occurs Table 3.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The effects of glyphosate on the EPSPS enzyme are known, but this inhibition affects other biochemical and physiological processes (Baylis, 2000), with differences among species such as Convolvulus arvensis (DeGennaro and Weller, 1984), Zea mays L. (Forlani & Racchi, 1995), Lolium rigidum Gaudin (Lorraine-Colwill et al, 2001), and Capsicum anuum (Ronco et al, 2008).…”
Section: Discussionmentioning
confidence: 99%